Wybrane aspekty sądowych i pozasądowych sposobów rozwiązywania indywidualnych sporów pracowniczych - Bakuń-Nawłoka, Urszula (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The problem of labour disputes is particularly important because it can affect any one of us. Labour disputes are inevitable in the course of business. When disputes arise, it is important that they are resolved quickly, using the best method that takes into account the interests of all parties, minimises negative consequences and does not involve high costs.
Keywords: employer; agreement; civil procedure; alternative method; judicial procedures